Serum Cardiac Troponin I Levels in Neonates with Perinatal Asphyxia; A Cross-Sectional Study - Asghar Marzban; Nahid Jafari; Mahnaz Zareakbari (Iranian Journal of Neonatology)
Background: Cardiac dysfunction is part of the clinical spectrum of multiple organ dysfunction in asphyxiated newborns. Cardiac troponin I (cTnI) is a biomarker linked to neonatal hypoxic-ischemic encephalopathy (HIE) that can help diagnose perinatal asphyxia and predict the severity of myocardial dysfunction. Therefore, the aim of the present study was to examine the serum levels of cTnI in resuscitated infants suffering from perinatal asphyxia.Methods: This cross-sectional study was performed on 84 resuscitated infants at Ayatollah Mousavi Hospital in Zanjan, Iran (December 2020-August 2021). A checklist was created that included the demographic data of the infants, Apgar scores at 1, 5, and 10 min, arterial blood gas (ABG) values, and cTnI levels at 72 h postpartum. Quantitative and qualitative variables were compared between the two groups using the independent t-test/Mann-Whitney U test and chi-square/Fisher’s exact tests.Results: Fifty-eight infants (69%) were male and 26 (31%) were female. The mean cTnI levels in infants who underwent advanced resuscitation (38.65 ± 65.63 pg/mL) were significantly higher than in infants who received early resuscitation and positive pressure ventilation (PPV) (18.60 ± 24.47 pg/mL) (p = 0.013). It was found that high cTnI levels were more prevalent among infants with base excesses (BEs) greater than -12 mEq/L and infants whose 5-min and 10-min Apgar scores were between 0 and 4 (p < 0.05). The results of quantile regression indicated that one week increase in gestational age and one unit rise in the Apgar score at 10 min, Apgar score at 5 min, pH, and BE were associated with a drop of 0.71 (p = 0.002), 1.70 (p = 0.005), 0.74 (p = 0.005), 2.85 (p = 0.025), and 0.33 (p = 0.005) pg/mL in cTnI levels, respectively.Conclusion: The results of our study revealed that blood cTnI levels were significantly higher in infants who underwent advanced resuscitation, suggesting that cardiac troponin may serve as a helpful marker in assessing myocardial injury in these individuals.